Cursor Control through Eye movement - Kashish, Shaikh Adiba; Ghodele, Nidhi; Waquas, Hashmi Syed; Tanzeel, Nabeela (International Journal of Computer Sciences and Engineering, 2022)
Eye tracking system has a suitable design which controls any devices which has digital screen with the eyeball movement and gesture without any help of required hardware. This technical concept has a potential to abolish and replace the standard mouse with the human eyes as a new way to interact and communicate with computer and also intended to replace standard computer screen pointing devices for the use of disable and handicapped people or as an alternative for using mouse which is very easy to use for faster input process. The system makes use of a PC webcam in order to detect eye movement. The system continuously scans camera input for pattern similar to the eye. Once the eye is detected, the system locks it as an object. The eye moment image is captured and transmitted by Raspberry Pi 3 model b and Microcontroller in order to process with OpenCV to derive the coordinator of the eyeball. The approach we described and defined is a real- time, non-intrusive, quick and cost-effective method of tracking facial features with the help of IR sensors.